X-ray study of Poly(vinyl Alcohol)-Iodine complex prepared from the dilute iodine solution as a hint to know the inner structure of polarizer. (26th October 2021) - Tashiro, Kohji; Takahama, Tomohiko; Wang, Meng Fan
Abstract: As well known, poly (vinyl alcohol) (PVA) forms the various kinds of iodine complexes (forms I, II and III) when the sample is immersed in the KI/I2 aqueous solution of various iodine concentrations of 0.1–3 M. By immersing the PVA sample in more dilute solution of 0.001–0.05 M, a new X-ray diffraction pattern has been found (form IV). The quantitative analysis of the X-ray diffraction pattern combined with the resonance Raman data and the density functional theoretical calculation allowed us to derive the concrete structure model of form IV. The vertically-arrayed linear I5 − ions are surrounded by the 6 PVA chains of planar-zigzag conformation to form the cylindrical structure. These cylinders are gathered together to form the hexagonal lattice. On the basis of the thus-determined structural information of a series of complexes, the transformation mechanism has been proposed for forms IV, I, II and III. Besides, the X-ray diffraction pattern of form IV was found to be similar to that measured for a commercial polarizer. The inner structure of the polarizer has been discussed concretely using the thus-revealed aggregation structure of form IV. Graphical abstract: Image 1 Highlights: A new crystal form IV was discovered for poly (vinyl alcohol)-iodine complex. Crystal structure of form IV has been analyzed by X-ray, Raman and DFT method. The inner structure of a commercial optical polarizer was derived concretely.